How to interview and conduct focus groups - Katz-Buonincontro, Jen (Concise guides to conducting behavioral, health, and social science research series, 2022)
"This book guides undergraduate and masters-level students through the steps to conducting a research project that uses personal interviews or focus groups. It provides tips on how to plan for and conduct the interview or focus group, and how to analyze the qualitative data.Readers will learn how interviews and focus groups are used in various research designs. They will explore coding, analysis, and reporting methods, along with key skills for avoiding bias and interacting. Tips for using technology ethically and appropriately are also included"--Provided by publisher.